A systematic review of the evidence on home care reablement services - Legg, Lynn; Gladman, John R.F.; Drummond, Avril E.R.; Davidson, Alex (SAGE, 2015)
Objective To determine whether publically funded ‘reablement services’ have any effect on patient health or use of services.